2008
DOI: 10.1007/s10038-008-0338-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of the SLC45A2 gene with physiological human hair colour variation

Abstract: Pigmentation is a complex physical trait with multiple genes involved. Several genes have already been associated with natural differences in human pigmentation. The SLC45A2 gene encoding a transporter protein involved in melanin synthesis is considered to be one of the most important genes affecting human pigmentation. Here we present results of an association study conducted on a population of European origin, where the relationship between two non-synonymous polymorphisms in the SLC45A2 gene -rs26722 (E272K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 44 publications
4
45
0
Order By: Relevance
“…In humans, SLC45A2 mutations are known to cause oculocutaneous albinism type 4 (OCA4) [137][138][139]. Common SNPs, including two non-synonymous SNPs in SLC45A2, rs16891982 (L374F, c.1122G>C) and rs26722 (E272K, c.814G>A), have been associated with normal variation in human skin, hair, and eye color in Europeans, South Asians, as well as in admixed individuals [126,[140][141][142][143]. The association of rs26722 may be explained by linkage disequilibrium with rs16891982 [142].…”
Section: Slc45a2mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, SLC45A2 mutations are known to cause oculocutaneous albinism type 4 (OCA4) [137][138][139]. Common SNPs, including two non-synonymous SNPs in SLC45A2, rs16891982 (L374F, c.1122G>C) and rs26722 (E272K, c.814G>A), have been associated with normal variation in human skin, hair, and eye color in Europeans, South Asians, as well as in admixed individuals [126,[140][141][142][143]. The association of rs26722 may be explained by linkage disequilibrium with rs16891982 [142].…”
Section: Slc45a2mentioning
confidence: 99%
“…Common SNPs, including two non-synonymous SNPs in SLC45A2, rs16891982 (L374F, c.1122G>C) and rs26722 (E272K, c.814G>A), have been associated with normal variation in human skin, hair, and eye color in Europeans, South Asians, as well as in admixed individuals [126,[140][141][142][143]. The association of rs26722 may be explained by linkage disequilibrium with rs16891982 [142]. The derived 374F allele is almost fixed in people of European descent, highly frequent in Uygurs from Urumqi (west China), and quite rare in the other populations examined [141,144].…”
Section: Slc45a2mentioning
confidence: 99%
“…The SLC45A2 gene, which encodes a transporter protein involved in melanin synthesis, is considered one of the most important genes affecting human pigmentation. [24] Our results showed that minor allele homozygotes (A) of rs35390 of SLC45A2 might beassociated (P = 0.007 and P = 8.877x10 -5 , in additive and recessive models, respectively; Table 5) with an increased absorption of simvastatin. SLC25A37 (Mitoferrin-1; Mfrn1), a member of the solute carrier family localized in the mitochondrial inner membrane, functions as an essential iron importer for the synthesis of mitochondrial heme and iron-sulfur clusters in erythroblasts.…”
Section: Discussionmentioning
confidence: 63%
“…Some genes implicated before in the genetics of hair and skin color did not reach our 11 most significant hits, but were also strongly stratified: TYR (tyrosinase precursor) [20] [16,19,21] , reached p = 3.1 ! 10 -36 .…”
Section: Genes Involved In Hair Skin and Eye Colormentioning
confidence: 99%